A method for preparing high-entropy boride ultrahigh-temperature ceramic powder by a liquid phase method
Patent Information
- Application Number
- CN202411532711.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2044-10-30
AI Technical Summary
但上述方法所使用的过渡金属氯化物或有机物前驱体的价格相较于过渡金属氧化物更为昂贵,糠醛、乙酰丙酮或共混烯丙基功能新聚树脂等较之于山梨醇等生物质糖类也增加了合成成本,对环境不友好
[0023] (1) This invention uses transition metal oxides as metal sources, boric acid as boron source, and sorbitol as carbon source to prepare green, low-cost, and controllable high-entropy boride ultra-high temperature ceramic powder by liquid phase method combined with borothermic/carbothermic reduction reaction.
Smart Images

Figure CN119430950B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of ceramic materials technology, specifically relating to a method for preparing high-entropy boride ultra-high temperature ceramic powder by liquid phase method. Background Technology
[0002] The statements herein provide only background information in relation to this invention and do not necessarily constitute prior art.
[0003] Ultra-high temperature ceramics refer to a class of ceramic materials that can maintain physical and chemical stability in harsh environments such as ultra-high temperatures (≥2000℃) and reaction atmospheres. They mainly include refractory metal carbides, borides, and nitrides. Transition metal diborides are a class of ceramic materials with excellent ultra-high temperature performance. They are typically composed of transition metals and boron, exhibiting significantly high melting points, excellent thermal stability, and extremely high hardness, but still suffer from low fracture toughness and insufficient oxidation resistance at ultra-high temperatures. High-entropy boride ultra-high temperature ceramics are a class of ceramic materials composed of multiple transition metal elements and boron, with their core characteristic being the high-entropy effect. This effect originates from the presence of four or more metal elements in the material, existing in equimolar ratios, thus forming a solid solution with a highly mixed composition. Due to the high-entropy effect, hysteresis diffusion effect, lattice distortion effect, and cocktail effect, high-entropy transition metal diboride ceramics possess even superior properties, such as higher hardness and better oxidation resistance. These properties enable high-entropy transition metal diborides to exhibit superior wear resistance and oxidation resistance under high temperature and high stress environments. Through precise synthesis and processing techniques, they can be used to manufacture key components such as ultra-high temperature cutting tools, nozzles, and thermal protection systems, which can be applied in aerospace, defense, metallurgy and other fields.
[0004] In the preparation of high-entropy boride ultra-high temperature ceramic bulks, single-component transition metal borides are typically used as raw materials, mechanically mixed via high-energy ball milling, followed by hot pressing or spark plasma sintering. However, the presence of oxide impurities can impair performance. Alternatively, borothermic / carbothermic reduction reactions using transition metal oxide powders, boron carbide, and carbon black as raw materials are a promising low-cost method for preparing bulk high-entropy boride ultra-high temperature ceramics. However, when carbon black is chosen as the carbon source, sufficient contact with the oxide powder cannot be guaranteed, and the resulting product may be non-uniform in composition or microstructure. The advantage of the liquid-phase method is that the starting materials can be uniformly mixed at the molecular level. Therefore, it is necessary to choose the liquid-phase method for preparing high-entropy ultra-high temperature ceramic powders. Traditional work uses transition metal chlorides or organic precursors as metal sources and furfural, acetylacetone, or blended allyl functionalized new polymers as carbon sources, employing a liquid polymer precursor route to prepare high-entropy ultra-high temperature ceramic powders with uniform elemental distribution. However, the transition metal chlorides or organic precursors used in the above methods are more expensive than transition metal oxides. Furfural, acetylacetone, or blended allyl functional new polymers also increase the synthesis cost compared to biomass sugars such as sorbitol, and are not environmentally friendly. Summary of the Invention
[0005] The purpose of this section is to outline some aspects of embodiments of the present invention and to briefly describe some preferred embodiments. Simplifications or omissions may be made in this section, as well as in the abstract and title of this application, to avoid obscuring the purpose of these documents; however, such simplifications or omissions should not be construed as limiting the scope of the invention.
[0006] In view of the problems existing in the above and / or prior art, the present invention is proposed.
[0007] Therefore, the purpose of this invention is to overcome the shortcomings of the prior art and provide a method for preparing high-entropy boride ultra-high temperature ceramic powder by liquid phase method.
[0008] To solve the above-mentioned technical problems, the present invention provides the following technical solution:
[0009] TiO2, ZrO2, HfO2, Nb2O5 and Ta2O5 powders are mixed evenly to obtain mixture I. Then ZrO2 ball milling beads and ethanol are added, and the mixture is ball milled and dried to obtain mixed powder.
[0010] Boric acid and sorbitol are dissolved in water to obtain solution I;
[0011] Acrylamide and N,N'-methylenebisacrylamide were added to solution I, stirred until homogeneous, and ammonia was added to adjust the pH to obtain solution II;
[0012] The mixed powder was added to solution II and dispersed evenly. Ammonium persulfate and tetramethylethylenediamine were added for gelation treatment to obtain a gel. The gel was heated to remove moisture and then heat-treated under an inert atmosphere to obtain a carbonized sample.
[0013] The carbonized sample was pulverized and sintered under an inert atmosphere, then naturally cooled to obtain high-entropy boride ultra-high temperature ceramic powder.
[0014] As a preferred embodiment of the method for preparing high-entropy boride ultra-high temperature ceramic powder by liquid phase method according to the present invention, wherein: in the mixture I, the molar ratio of TiO2, ZrO2, HfO2, Nb2O5 and Ta2O5 is 2:2:2:1:1 to 1.1, and the particle size is <10μm.
[0015] In a preferred embodiment of the method for preparing high-entropy boride ultra-high temperature ceramic powder by liquid phase method according to the present invention, the mass ratio of ethanol to mixed powder is 1 to 5:1, the ball milling speed is 200 to 300 r / min, and the time is 12 to 24 h.
[0016] In a preferred embodiment of the method for preparing high-entropy boride ultra-high temperature ceramic powder by liquid phase method according to the present invention, the diameter of the ZrO2 ball milling beads is 1-10 mm, and the mass ratio of the ZrO2 ball milling beads to the mixed powder is 2-10:1.
[0017] In a preferred embodiment of the method for preparing high-entropy boride ultra-high temperature ceramic powder by liquid phase method according to the present invention, the molar ratio of boric acid, sorbitol and mixture I is 20-30:9-15:2.
[0018] In a preferred embodiment of the liquid-phase method for preparing high-entropy boride ultra-high temperature ceramic powder according to the present invention, the concentration of acrylamide in solution II is 0.3-0.5 g / L, and the mass ratio of acrylamide to N,N'-methylenebisacrylamide is 10-15:1.
[0019] In a preferred embodiment of the method for preparing high-entropy boride ultra-high temperature ceramic powder by liquid phase method according to the present invention, the concentration of the mixed powder in solution II is 0.1-0.5 g / mL.
[0020] In a preferred embodiment of the method for preparing high-entropy boride ultra-high temperature ceramic powder by liquid phase method according to the present invention, the addition of ammonia water to adjust the pH is to adjust the pH to 8-9.
[0021] In a preferred embodiment of the liquid-phase method for preparing high-entropy boride ultra-high temperature ceramic powder according to the present invention, the mass ratio of ammonium persulfate to tetramethylethylenediamine is 1:1 to 1.2, and the concentration of ammonium persulfate in solution II is 0.8 to 1.0 g / L.
[0022] In a preferred embodiment of the method for preparing high-entropy boride ultra-high temperature ceramic powder by liquid phase method according to the present invention, the inert atmosphere is nitrogen or argon; the heat treatment temperature is 500-600℃, and the holding time is 1-2 hours; the sintering temperature is 2000-3000℃, and the holding time is 1-4 hours. Beneficial effects of the present invention:
[0023] (1) This invention uses transition metal oxides as metal sources, boric acid as boron source, and sorbitol as carbon source to prepare green, low-cost, and controllable high-entropy boride ultra-high temperature ceramic powder by liquid phase method combined with borothermic / carbothermic reduction reaction.
[0024] (2) The present invention uses ammonium sulfate, tetramethylethylenediamine, acrylamide, and N,N'-methylenebisacrylamide for gelation treatment to successfully synthesize pure phase high entropy boride ultra-high temperature ceramic powder. Attached Figure Description
[0025] To more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings used in the description of the embodiments and comparative examples will be briefly introduced below. Obviously, the drawings described below are only some embodiments and comparative examples of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort. Wherein:
[0026] Figure 1 The high entropy (Ti) obtained in Example 1 of this invention 0.2 Zr 0.2 Hf 0.2 Nb 0.2 Ta 0.2 X-ray diffraction pattern of B2 powder.
[0027] Figure 2 The high entropy (Ti) obtained in Example 1 of this invention 0.2 Zr 0.2 Hf 0.2 Nb 0.2 Ta 0.2 Scanning electron microscope image of B2 powder.
[0028] Figure 3 The X-ray diffraction pattern is shown for the powder prepared at 1900℃ in Comparative Example 1 of this invention. Detailed Implementation
[0029] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, the specific embodiments of the present invention will be described in detail below with reference to the examples in the specification.
[0030] Many specific details are set forth in the following description in order to provide a full understanding of the invention. However, the invention may also be practiced in other ways different from those described herein, and those skilled in the art can make similar extensions without departing from the spirit of the invention. Therefore, the invention is not limited to the specific embodiments disclosed below.
[0031] Secondly, the term "one embodiment" or "embodiment" as used herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The phrase "in one embodiment" appearing in different places in this specification does not necessarily refer to the same embodiment, nor is it a single or selective embodiment that is mutually exclusive with other embodiments.
[0032] Unless otherwise specified, all raw materials used in this invention are commercially available in the field.
[0033] Example 1
[0034] This embodiment provides a method for preparing high-entropy boride ultra-high temperature ceramic powder using a liquid phase method.
[0035] 1) Five transition metal oxide powders, TiO2, ZrO2, HfO2, Nb2O5, and Ta2O5, were mixed in a molar ratio of 2:2:2:1:1, with corresponding mass values of 1.5976 g, 2.4646 g, 4.2140 g, 2.6608 g, and 4.4233 g, respectively. All powders had a particle size <10 μm, and the total oxide powder weight was approximately 15.36 g. The mixed powder was then placed in a ball mill jar, and 30 g of 5 mm diameter ZrO2 grinding beads were added (ZrO2 grinding beads to mixed powder mass ratio 2:1). 20 mL of ethanol was added (ethanol to mixed powder mass ratio 4:3). The mixture was ball milled at 250 rpm for 12 h. The ethanol was removed in an 80℃ oven, and the transition metal oxide mixed powder was collected.
[0036] 2) Add 0.3 mol boric acid and 0.15 mol sorbitol to 100 mL of deionized water. The molar ratio of boric acid, sorbitol and mixed powder is 10:5:1. Stir at 60 °C until dissolved to obtain solution I.
[0037] 3) Add 30g of acrylamide and 2g of N,N'-methylenebisacrylamide to solution I. The concentrations of acrylamide and N,N'-methylenebisacrylamide in solution II are 0.3g / mL and 0.02g / mL, respectively, with a mass ratio of 15:1. Add ammonia dropwise to adjust the pH of the solution to 9 to obtain solution II.
[0038] 4) Add the mixed powder to 150 mL of solution II. The concentration of the mixed powder is 0.1 g / mL. Sonicate for 10 minutes and stir for 20 minutes. Add 0.12 g of ammonium persulfate and 0.12 g of tetramethylethylenediamine. The concentration of each in solution II is 0.8 g / L. Continue stirring to achieve gelation. Transfer the gel to an oven at 120℃ and keep it at that temperature for 10 h to remove moisture. Then, put it into a tube furnace for heat treatment. Purge with argon gas and heat to 600℃ at a rate of 10℃ / min. Keep it at that temperature for 2 h and let it cool naturally to room temperature to obtain the carbonized sample.
[0039] 5) The carbonized sample was crushed, placed in a graphite crucible, and then placed in a high-temperature atmosphere furnace. Argon gas was introduced, and the temperature was raised to 2000℃ at a rate of 10℃ / min for sintering. The temperature was held for 1 hour, and then naturally cooled to room temperature to obtain high-entropy boride ultra-high temperature ceramic powder, denoted as (Ti). 0.2 Zr 0.2 Hf 0.2 Nb 0.2 Ta 0.2 )B2.
[0040] Figure 1 For (Ti) 0.2 Zr 0.2 Hf 0.2 Nb 0.2 Ta 0.2 The X-ray diffraction pattern of B2 powder indicates that the product has achieved sufficient high entropy. Figure 2 For (Ti) 0.2 Zr 0.2 Hf 0.2 Nb 0.2 Ta 0.2 Scanning electron microscope image of B2 powder.
[0041] Example 2
[0042] The difference between this embodiment and Embodiment 1 is that the sintering temperature in step 5) is adjusted to 3000℃, while the other steps are the same as in Embodiment 1, to obtain high-entropy boride ultra-high temperature ceramic powder.
[0043] Example 3
[0044] The difference between this embodiment and Example 1 is that in step 3), the concentration of acrylamide in solution II is adjusted to 0.5 g / mL, and the concentration of N,N'-methylenebisacrylamide in solution II is adjusted to 0.05 g / mL, with a mass ratio of 10:1. The other steps are the same as in Example 1, and high-entropy boride ultra-high temperature ceramic powder is obtained.
[0045] Comparative Example 1
[0046] The difference from Example 1 is that the amount of boric acid used in step 2) is adjusted to 0.2 mol, while the other steps are the same as in Example 1.
[0047] Carbides were found in the product, making it impossible to obtain high-entropy boride ceramic powder.
[0048] The high-entropy borides obtained in this invention rely on a chemical reaction involving an oxide, a carbon source, and a boron source at high temperature to form borides. Boric acid, as the boron source, decomposes at high temperature to produce boron oxide, which volatilizes at high temperatures; therefore, an excess of boron source is required in the actual reaction. When the boric acid content is insufficient but the carbon source is sufficient, the chemical reaction producing high-entropy borides cannot occur fully, and the residual carbon source and residual oxide react to form carbide impurities.
[0049] Comparative Example 2
[0050] The difference from Example 1 is that the amount of sorbitol in step 2) is adjusted to 0.1 mol, while the other steps are the same as in Example 1.
[0051] The product contains residual oxides, making it impossible to obtain high-entropy boride ceramic powder.
[0052] The high-entropy borides obtained in this invention rely on a chemical reaction involving an oxide, a carbon source, and a boron source at high temperature to generate borides. As a carbon source, sorbitol decomposes at high temperature to produce carbon. When the carbon content is insufficient, the chemical reaction producing high-entropy borides cannot occur fully, ultimately leaving unreacted oxides.
[0053] Comparative Example 3
[0054] The difference from Example 1 is that in step 3), no acrylamide or N,N'-methylenebisacrylamide is added; the other steps are the same as in Example 1.
[0055] The solution remained in a liquid state and did not gel, making it impossible to obtain high-entropy boride ceramic powder.
[0056] Comparative Example 4
[0057] The difference from Example 1 is that ammonia is not added in step 3) to adjust the pH, while the other steps are the same as in Example 1.
[0058] The solution remains in a liquid state for a long time, making it difficult to achieve gelation and thus impossible to obtain high-entropy boride ceramic powder.
[0059] Gelation is necessary to achieve uniform mixing of ceramic powder with carbon sources, boron sources, etc. Only after gelation can subsequent carbonization and sintering steps be carried out to obtain high-entropy boride ceramic powder.
[0060] Comparative Example 5
[0061] The difference from Example 1 is that in step 4), ammonium persulfate or tetramethylethylenediamine is not added, while the other steps are the same as in Example 1.
[0062] The solution remained in a liquid state and did not gel, making it impossible to obtain high-entropy boride ceramic powder.
[0063] Comparative Example 6
[0064] The difference from Example 1 is that the sintering temperature in step 5) is adjusted to 1900°C, while the other steps are the same as in Example 1.
[0065] Figure 3 The XRD test results show that the main phase is a high-entropy diboride ceramic phase, and there are phases that are not fully high-entropy.
[0066] Compared to Example 1, the compound in this comparative example contains an insufficiently entropy-modified ceramic phase. Therefore, controlling the sintering temperature is crucial in the preparation of high-entropy boride ultra-high temperature ceramic powders.
[0067] In summary, this invention uses transition metal oxides as the metal source, boric acid as the boron source, and sorbitol as the carbon source, employing a liquid-phase method combined with borothermic / carbothermic reduction reactions to prepare green, low-cost, and controllable high-entropy boride ultra-high temperature ceramic powders. Furthermore, this invention successfully synthesizes pure-phase high-entropy boride ultra-high temperature ceramic nanoparticles through gelation treatment using ammonium sulfate, tetramethylethylenediamine, acrylamide, and N,N'-methylenebisacrylamide.
[0068] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention and are not intended to limit it. Although the present invention has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of the present invention without departing from the spirit and scope of the technical solutions of the present invention, and all such modifications or substitutions should be covered within the scope of the claims of the present invention.
Claims
1. A method for preparing high-entropy boride ultra-high temperature ceramic powder by liquid phase method, characterized in that: include, TiO2, ZrO2, HfO2, Nb2O5 and Ta2O5 powders are mixed evenly to obtain mixture I. Then ZrO2 ball milling beads and ethanol are added, and the mixture is ball milled and dried to obtain mixed powder. Boric acid and sorbitol are dissolved in water to obtain solution I; Acrylamide and N,N'-methylenebisacrylamide were added to solution I, stirred until homogeneous, and ammonia was added to adjust the pH to obtain solution II; The mixed powder was added to solution II and dispersed evenly. Ammonium persulfate and tetramethylethylenediamine were added for gelation treatment to obtain a gel. The gel was heated to remove moisture and then heat-treated under an inert atmosphere to obtain a carbonized sample. The carbonized sample was pulverized and sintered under an inert atmosphere, then naturally cooled to obtain high-entropy boride ultra-high temperature ceramic powder. In the mixture I, the molar ratio of TiO2, ZrO2, HfO2, Nb2O5, and Ta2O5 is 2:2:2:1:1 to 1.1, and the particle size is <10µm. The molar ratio of boric acid, sorbitol and the mixed powder is 20-30:9-15:2; The inert atmosphere is nitrogen or argon gas; the heat treatment temperature is 500–600°C and the holding time is 1–2 hours; the sintering temperature is 2000–3000°C and the holding time is 1–4 hours.
2. The method for preparing high-entropy boride ultra-high temperature ceramic powder by liquid phase method as described in claim 1, characterized in that: The mass ratio of ethanol to the mixed powder is 1 to 5:1, the ball milling speed is 200 to 300 r / min, and the time is 12 to 24 h.
3. The method for preparing high-entropy boride ultra-high temperature ceramic powder by liquid phase method as described in claim 1, characterized in that: The diameter of the ZrO2 grinding beads is 1-10 mm, and the mass ratio of the ZrO2 grinding beads to the mixed powder is 2-10:
1.
4. The method for preparing high-entropy boride ultra-high temperature ceramic powder by liquid phase method as described in claim 1, characterized in that: The concentration of acrylamide in solution II is 0.3–0.5 g / L, and the mass ratio of acrylamide to N,N'-methylenebisacrylamide is 10–15:
1.
5. The method for preparing high-entropy boride ultra-high temperature ceramic powder by liquid phase method as described in claim 1, characterized in that: The concentration of the mixed powder in solution II is 0.1–0.5 g / mL.
6. The method for preparing high-entropy boride ultra-high temperature ceramic powder by liquid phase method as described in claim 1, characterized in that: The addition of ammonia to adjust the pH is to adjust the pH to 8-9.
7. The method for preparing high-entropy boride ultra-high temperature ceramic powder by liquid phase method as described in claim 1, characterized in that: The mass ratio of ammonium persulfate to tetramethylethylenediamine is 1:1 to 1.2, and the concentration of ammonium persulfate in solution II is 0.8 to 1.0 g / L.
Citation Information
Patent Citations
High-entropy oxide submicron powder and preparation method thereof
CN110903084A
Preparation method of high-entropy boride infrared radiation material
CN117466650A